2019
DOI: 10.3390/ijms20030754
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Koumine, an Alkaloid from Gelsemium Sempervirens, on Injury Induced by H2O2 in IPEC-J2 Cells

Abstract: Medicinal herbal plants have been commonly used for intervention in different diseases and improvement of health worldwide. Koumine, an alkaloid monomer found abundantly in Gelsemium plants, can be effectively used as an antioxidant. The purpose of this study was to evaluate the potential protective effect of koumine against hydrogen peroxide (H2O2)-induced oxidative stress and apoptosis in porcine intestinal epithelial cell line (IPEC-J2 cells). MTT assays showed that koumine significantly increased cell viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
(24 reference statements)
3
17
0
2
Order By: Relevance
“…Although many studies have attempted to explore the therapeutic effect and mechanism of KM in diseases ( Qiu et al, 2015 ; Yang et al, 2016 ; Yuan et al, 2016b ; Chen et al, 2017 ; Jin et al, 2018a ; Jin et al, 2018b ; Jin et al, 2019 ; Yuan et al, 2019a ; Yuan et al, 2019b ; Yue et al, 2019 ), its effect on NLRP3 inflammasome activation and the underlying mechanism remain unknown. In this study, we identified KM as a broad-spectrum inhibitor of NLRP3 inflammasome activation that inhibited NLRP3 inflammasome activation both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have attempted to explore the therapeutic effect and mechanism of KM in diseases ( Qiu et al, 2015 ; Yang et al, 2016 ; Yuan et al, 2016b ; Chen et al, 2017 ; Jin et al, 2018a ; Jin et al, 2018b ; Jin et al, 2019 ; Yuan et al, 2019a ; Yuan et al, 2019b ; Yue et al, 2019 ), its effect on NLRP3 inflammasome activation and the underlying mechanism remain unknown. In this study, we identified KM as a broad-spectrum inhibitor of NLRP3 inflammasome activation that inhibited NLRP3 inflammasome activation both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Under LPS challenge, TLR4 binds to nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 4 and further promotes the production of ROS-induced NF-κB activation ( Park et al, 2004 ). KM is an antioxidant agent that maintains the mitochondrial membrane potential in porcine intestinal epithelial cells ( Yuan et al, 2019b ). We confirmed that KM can exert NLRP3 inhibitory activity by eliminating ROS generation in response to stimulation with LPS plus ATP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koumine (KM), the most abundant alkaloid in Gelsemium elegans Benth. ( G. elegans ) has various pharmacological properties and is known to be effective in the treatment of numerous age-associated conditions including postoperative pain ( Xiong et al., 2017 ; Shoaib et al., 2019 ), inflammation ( Yuan et al., 2016 ; Wu et al., 2020 ), rheumatoid arthritis ( Yang et al., 2016 ), malignant tumors ( Yuan et al., 2019a ), nonalcoholic fatty liver disease ( Yue et al., 2019 ), oxidative stress ( Yuan et al., 2019b ), and neuropathic pain ( Jin et al., 2018a ; Jin et al., 2018b ). However, the pharmacokinetic profile of KM in the elderly or aged animals remains to be fully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The small intestine is particularly vulnerable to be damaged by DON. Exposure to DON can give rise to augment intestinal permeability (Pinton et al, 2010), the irritation or necrosis of intestinal mucosa (Pestka, 2007), cell apoptosis (Pestka, 2008), low antioxidative capacity and mitochondrial dysfunction (Yuan et al, 2019), resulting in intestinal damage in pigs. Tight junctions are the junctional multiprotein complexes, which mainly sustain the intestinal epithelial barrier (Ashida, Ogawa, Kim, Mimuro, & Sasakawa, 2011).…”
Section: Introductionmentioning
confidence: 99%